2011
DOI: 10.1088/0026-1394/48/1a/08015
|View full text |Cite
|
Sign up to set email alerts
|

International comparison CCQM-K76: Sulfur dioxide in nitrogen

Abstract: The key comparison CCQM-K76 was designed to test the capabilities of the participants to measure and certify sulfur dioxide in nitrogen, and to provide supporting evidence for the CMCs of these institutes for sulfur dioxide. Also, as sulfur dioxide is designated a core compound, and the 100 µmol/mol concentration is within the designated core compound concentration range, this comparison was also designed to demonstrate core capabilities of institutes which qualify under the rules of the Gas Analysis Working G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A 'model 2' key comparison mimics the provision of a certified reference material, and for the mixtures concerning in this paper, these uncertainty budgets are based on ISO 6142-1 [20], describing the preparation of calibration gas mixtures by static gravimetry. Examples of uncertainty budgets for gravimetrically prepared gas mixtures in 'model 2' key comparisons have been published in the measurement reports in CCQM-K82 (methane in air) [19] and CCQM-K120 (carbon dioxide in air) [26], and those for the analysis ('model 1') key comparisons in the measurement reports in, e.g., CCQM-K76 (sulphur dioxide in nitrogen) [28] and CCQM-K111 (propane in nitrogen) [13].…”
Section: Participation In Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 'model 2' key comparison mimics the provision of a certified reference material, and for the mixtures concerning in this paper, these uncertainty budgets are based on ISO 6142-1 [20], describing the preparation of calibration gas mixtures by static gravimetry. Examples of uncertainty budgets for gravimetrically prepared gas mixtures in 'model 2' key comparisons have been published in the measurement reports in CCQM-K82 (methane in air) [19] and CCQM-K120 (carbon dioxide in air) [26], and those for the analysis ('model 1') key comparisons in the measurement reports in, e.g., CCQM-K76 (sulphur dioxide in nitrogen) [28] and CCQM-K111 (propane in nitrogen) [13].…”
Section: Participation In Comparisonsmentioning
confidence: 99%
“…In practice, it is sometimes observed that the standard uncertainty thus obtained does not fully explain the dispersion of the three measured values in a key comparison. As of CCQM-K76 [28], this assessment is part of the uncertainty evaluation. In the beginning, the standard deviation of the three measured values was combined with the standard uncertainty computed from the ISO 6143 procedure.…”
Section: Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The filled circles show the results from five track A key comparisons (CCQM-K52: 360 µmol mol −1 carbon dioxide in air [7], CCQM-K53: 100 µmol mol −1 oxygen in nitrogen [8], CCQM-K76: 100 µmol mol −1 sulphur dioxide in nitrogen [9], CCQM-K111: 1000 µmol mol −1 propane in nitrogen [10] and CCQM-K120: 800 µmol mol −1 carbon dioxide in air [11]). Figure 1 does not show the results from comparisons at 380 and 480 µmol mol −1 from CCQM-K120 as they fall outside track A.…”
Section: Benchmarking the Success Of Key Comparisonsmentioning
confidence: 99%